Aggressiveness in depression: a neglected symptom possibly associated with bipolarity and mixed features. (25th July 2017) - Verdolini, N.; Perugi, G.; Samalin, L.; Murru, A.; Angst, J.; Azorin, J.‐M.; Bowden, C. L.; Mosolov, S.; Young, A. H.; Barbuti, M.; Guiso, G.; Popovic, D.; et al.
Abstract : Objective: To evaluate aggressiveness during a major depressive episode (MDE) and its relationship with bipolar disorder (BD) in a post hoc analysis of the BRIDGE‐II‐MIX study. Method: A total of 2811 individuals were enrolled in this multicenter cross‐sectional study. MDE patients with (MDE‐A, n = 399) and without aggressiveness (MDE‐N, n = 2412) were compared through chi‐square test or Student's t ‐test. A stepwise backward logistic regression model was performed. Results: MDE‐A group was more frequently associated with BD ( P < 0.001), while aggressiveness was negatively correlated with unipolar depression ( P < 0.001). At the logistic regression, aggressiveness was associated with the age at first depressive episode ( P < 0.001); the severity of mania ( P = 0.03); the diagnosis of BD ( P = 0.001); comorbid borderline personality disorder (BPD) ( P < 0.001) but not substance abuse ( P = 0.63); no current psychiatric treatment ( P < 0.001); psychotic symptoms ( P = 0.007); the marked social/occupational impairment ( P = 0.002). The variable most significantly associated with aggressiveness was the presence of DSM‐5 mixed features ( P < 0.001, OR = 3.815). After the exclusion of BPD, the variable of lifetime suicide attempts became significant ( P = 0.013, OR = 1.405). Conclusion: Aggressiveness seems to be significantly associated with bipolar spectrum disorders, independently from BPD and substance abuse. Aggressiveness should be considered as a diagnostic criterion for the mixed features specifier and a target of tailored treatment strategy.